Obama and the Middle East : the end of America's moment? - Gerges, Fawaz A., 1958- (New York, NY : Palgrave Macmillan, 2012)
"During his presidential campaign, Barack Obama promised to distance the United States from the neoconservative foreign policy legacy of his predecessor, George W. Bush, and usher in a new era of a global, interconnected world. More than two years have passed since his inauguration, and the reality of President Obama's approach is in stark contrast to the ebullient and optimistic image that he originally built up. In fact, Obama is not committed to redefining U.S. foreign policy in a transformational way, but to calibrating and correcting the Bush policies, and reclaiming the neorealist approach that defined America's foreign policy since WWII. Taking stock of Obama's first year in the White House, this book places his engagement in the Middle East within the broader context of U.S. foreign policy since 9/11 and examines key areas that have posed a challenge to his administration. Middle East expert Fawaz Gerges highlights the administration's widening credibility gap and lack of resolve and political will to directly confront policy challenges head-on, and offer essential strategic recommendations for advancing U.S. relations with the Muslim world"--
Includes bibliographical references and index.
Keywords: Obama, Barack; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- 2009-; United States -- Foreign relations -- 2001-2009.